Parkinson's disease prevalence in Fabry disease: A survey study - Adina H. Wise; Amy Yang; Hetanshi Naik; Chanan Stauffer; Natasha Zeid; Christopher Liong; Manisha Balwani; Robert J. Desnick; Roy N. Alcalay (Molecular Genetics and Metabolism Reports, 2018)
Recent research has suggested a possible link between Parkinson's disease (PD) and Fabry disease. To test this relationship, we administered a self-report and family history questionnaire to determine the prevalence of PD in Fabry disease patients and family members with likely pathogenic alpha-galactosidase A (GLA) mutations. A total of 90 Fabry patients (77 from the online survey and 13 from the Icahn School of Medicine at Mount Sinai (ISMMS)) were included in the analysis. Two of the Fabry disease patients who completed the online survey were diagnosed with PD (2/90, 2.2%). Among probands older than 60, 8.3% (2/24) were diagnosed with PD. Using Kaplan Meier survival analysis, the age-specific risk of PD by age 70 was 11.1%. Family history was available on 72 Fabry families from the online study and 9 Fabry families from ISMMS. Among these 81 families, 6 (7.4%) had one first degree relative who fit the criteria for a conservative diagnosis of PD. The results of this study suggest that there may be an increased risk of developing PD in individuals with GLA mutations, but these findings should be interpreted with caution given the limitations of the study design.